The evaluation of microstructure of carbon/carbon composites generated by ultra-high temperature treatment towards excellent electromagnetic interference shielding property. (30th June 2022) - Xue, Kun; Fang, Lin; Zhang, Guangxi; Yu, Mingming; Ren, Musu; Sun, Jinliang; Zhang, Liying; Wei, Lianfeng; Xie, Wang
Abstract: Due to the need of electromagnetic shielding materials for satellites, carbon/carbon (C/C) composites have become a research focus due to their excellent properties. In this study, the ultrahigh treatment temperature was raised from 2500 °C to 2700 °C and 3000 °C, and the influence of micromorphology on the mechanical and electromagnetic shielding properties of materials was explored with an innovative image recognition method. The porosity of the C/C composites increased with increasing heat treatment temperature, from 6.95% to 8.65% after 3000 °C. The density decreased, and the graphitization degree increased gradually, indicating an improvement in the texture order degree. For the compression properties of the material, the Z direction after treatment at 3000 °C maintained a high compressive strength of 171 MPa. The electromagnetic interference (EMI) shielding efficiency (SE) of the C/C composites, which is completely consistent with the trend of electrical conductivity, increased with increasing heat treatment temperature, and the EMI SE of the C/C composites reached ∼80 dB after 3000 °C. It was found that reflection was the dominant EMI shielding mechanism of C/C composite materials. By comparing the comprehensive data indexes of C/C composites with other materials, the composites are expected to be a new generation of satellites with electromagnetic shielding material. Graphical abstract: Image 1